Manajemen Strategis Lingkungan Hidup: Kasus Bapedalda Kota Palembang - Commar, Muh. Andhy Syamsul (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2001)
In the past. enviromental management in Indonesia had always been handled by central government. With the wave of reforms and the implementation of decentralisation policy, local governments are now challenged to manage and tackle environmental problems on their own. In line with this current policy change and situation, the city council of Palembang has enacted Local Act (Perda) No.1 of 1999 and established Local Environmental Control Agency (Bapedalda). The main task of Bapedalda is to control environmental hazards and maintain a good level of environment conditions. Findings from this preliminary study show that environmental problems might become more serious with the decentralization policy as most of local governments does not have adequate attention to the environmental degradations. In The case of Palembang, although Bapedalda has a good potential in terms of human resources, technology, and budget, many of the local environmental problems cannot be 4nanaged properly. The function of Bapedalda is still impeded by lack of commitment among the local top authority, development policy that is concerned more on industry and economic aspects, and lack of public support and participation on environment preservation due to negative cultural attitude. In the near future, there are some strategies to be taken by Bapedalda, namely: 1) to set up a standard for environment quality and to identify the main sources of pollutions, 2) to build close cooperation with other local agencies and to improve skills in environment management, and 3) to improve public participation in environment management.